Promotion of Mental Health Rehabilitation in China: Community- Based Mental-Health Services - Youwei Zhu (Eco-Vector, 2020)
Community-based mental health services are important for the treatment and recovery of patients with mental health disorders. The Chinese government has made the establishment of a highly eﬃcient community-based health service an enduring priority. Since the 1960s, community-based mental health services have been developed in many Chinese cities and provinces. National policies, including mental health regulations and ﬁve-year national mental health working plans, have been issued to support the development of quality of mental health services. The accessibility and eﬃciency of community-based mental health services are now highly promoted to community residents.